2014
DOI: 10.1152/ajpregu.00382.2013
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of myosin regulatory light chain has minimal effect on kinetics and distribution of orientations of cross bridges of rabbit skeletal muscle

Abstract: Force production in muscle results from ATP-driven cyclic interactions of myosin with actin. A myosin cross bridge consists of a globular head domain, containing actin and ATP-binding sites, and a neck domain with the associated light chain 1 (LC1) and the regulatory light chain (RLC). The actin polymer serves as a "rail" over which myosin translates. Phosphorylation of the RLC is thought to play a significant role in the regulation of muscle relaxation by increasing the degree of skeletal cross-bridge disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
2
8
0
Order By: Relevance
“…The intensity of the absorption maxima band for the SF8(DDDDG) 2 sample was essentially unchanged after one hour of constant photon‐intense irradiation whereas absorption intensities for the Cy5 and Alexa Fluor 647 samples were reduced to 33 % and 77 % respectively (Figure S16). The enhanced photostability of the SF8 probe compared to Alexa Fluor 647 is notable and consistent with a previous report that a squaraine rotaxane was 4.2 times more photostable than Alexa Fluor 647 [32] …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The intensity of the absorption maxima band for the SF8(DDDDG) 2 sample was essentially unchanged after one hour of constant photon‐intense irradiation whereas absorption intensities for the Cy5 and Alexa Fluor 647 samples were reduced to 33 % and 77 % respectively (Figure S16). The enhanced photostability of the SF8 probe compared to Alexa Fluor 647 is notable and consistent with a previous report that a squaraine rotaxane was 4.2 times more photostable than Alexa Fluor 647 [32] …”
Section: Resultssupporting
confidence: 91%
“…Over the intervening years, we and others have successfully converted squaraine rotaxanes into targeted fluorescence imaging probes for use in cell microscopy and in vivo imaging of living subjects. Notably, independent labs have reported data suggesting that molecular probes with appended squaraine rotaxane dyes exhibit unsurpassed photostability for deep‐red single‐fluorescent‐molecule tracking and extremely high brightness for one and two‐photon fluorescence imaging [31–33] . Squaraine rotaxane dyes are now commercially available as reagents for bioconjugation and they have been used successfully to label antibodies and large proteins [31, 34] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Greenberg et al (2009) showed that phosphorylated crossbridges detach more slowly than unphosphorylated cross-bridges, thus increasing cross-bridge duty cycle (cf. Duggal et al, 2014). Alternatively, Greenberg et al (2010) showed that phosphorylation may increase the rigidity of the light chain-binding domain, thus increasing cross-bridge stiffness.…”
Section: Myosin Rlc Phosphorylationmentioning
confidence: 99%
“…(Figure modified from Fig. 6c of Farman et al 2009) Model based on skeletal muscle (Duggal et al 2014; Midde et al 2013) and cardiac muscle (Kampourakis and Irving 2015). In this model, without RLC phosphorylation, the myosin S1 and RLC regions are in conformational equilibrium between lying/binding to the thick filament backbone surface (OFF state) and moving away towards thin filament (ON state) controlled by the RLC and the thick filament surface.…”
Section: Structure Isoforms Phosphorylation Sites and Function Of Rlcmentioning
confidence: 99%
“…Upon RLC phosphorylation, the myosin S1 head domain and the S1 RLC region are more disordered compared to non-phosphorylated RLC. However, Duggal et al reported that in skeletal muscle, RLC phosphorylation has a minimal effect on the ordering of the myosin S1 head domains or their distribution (Duggal et al 2014). These contrasting results highlight the need for a better understanding of the role of RLC phosphorylation and that RLC phosphorylation may have different consequence in different tissues or animal systems.…”
Section: Structure Isoforms Phosphorylation Sites and Function Of Rlcmentioning
confidence: 99%